Birds of America - Moore, Lorrie (Faber and Faber, 1988)
Beginning with a story about a second-rate film actress involved with a mechanic who has not the least idea who she was as an actress or is as a human being, this is a series of portraits of the young, the hip, the lost, the unsettled and the unhinged of modern-day America.